Finanzas personales y bienestar financiero en comerciantes del centro de abastos mercado "La Casona de Belén", periodo Iquitos 2022 - Ubilluz Portocarrero, Nathaly (2022)
The objective of the research was to determine the relationship between personal finances and financial well-being in merchants of the market supply center "La Casona de Belén" Iquitos period 2022, where a descriptive-correlational research and non-experimental design was chosen, made up of a study sample of 234 merchants, to whom the survey technique and the questionnaire as an instrument were applied. After the results, it was determined that the personal finances of the merchants are being carried out on a regular basis, because they almost never keep some type of record of income and expenses, as well as the banks almost never offer financial products to be able to invest, however Sometimes he takes advantage of the sources of income to invest in a timely manner, and has a contingency plan to cover unexpected expenses. He also sometimes identifies the excess of his income to be used for savings. On the other hand, financial well-being is qualified as medium, because sometimes merchants feel financial peace of mind, as having a credit card is sometimes essential for their lives, likewise, showing a good attitude in the face of a financial problem is sometimes important. . To conclude, the relationship between personal finances and financial well-being is considerable positive, with a coefficient and a significance of (r=0.840; p=0.01).